FOXID-EGG: PENGEMBANGAN INDUSTRI NUTRACEUTICAL BERBASIS TELUR ITIK LOKAL KAYA OMEGA-3 - Andri, Faizal; Sukoco, Aji; Hilman, Taufich; Susilo, Hadi; Sibawi, Sibawi (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Cardiovascular disease is the number one cause of death and disability worldwide. The purpose of this experiment was to create local ducks egg enriched with omega-3 as a candidate of nutraceutical to prevent cardiovascular disease. Sixty local ducks were randomly distributed to six treatment with three levels of fish oil (0 ppm, 1500 ppm, and 3000 ppm) and two levels of tomato meal (0 ppm and 150 ppm) in a 3x2 factorial arrangement. Data of local ducks performances were analyzed using two-way Anova, data of egg yolk omega-3 fatty acid content was analyzed descriptively. There was an interaction (p<0.05) of fish oil and tomato meal supplementation on egg weight. Supplementation of 3000 ppm fish oil +150 ppm tomato meal tend to increase DHA content of egg yolk with 0,43% compare than control treatment with 0,18%. The conclusion of this research supplementation of 3000 ppm fish oil +150 ppm tomato meal could produce egg yolk of local ducks egg with 0,04% ALA and 0,43% DHA.Keywords: Â cardiovascular disease, DHA, local ducks egg, fish oil, tomato meal